Trophy hunting in Africa: long‐term trends in antelope horn size. (5th April 2013) - Crosmary, W.‐G.; Loveridge, A. J.; Ndaimani, H.; Lebel, S.; Booth, V.; Côté, S. D.; Fritz, H.
Abstract Trophy hunting in ungulates may favour individuals with smaller horns. A decrease in horn/antler size may jeopardize the conservation potential of hunting areas, which would be a major concern in Africa where hunting zones represent over half of the total area of protected lands. We investigated horn length trends of harvested male impalas Aepyceros melampus, greater kudus Tragelaphus strepsiceros and sable antelopes Hippotragus niger, from 1974 to 2008 in Matetsi Safari Area, Zimbabwe. Horn length declined by 4% in impalas, partly because male harvest age decreased. In greater kudus, surprisingly, horn length increased by 14%, while mean age of harvested male greater kudus increased during the study period. Reduced hunting pressure on this species during the study may have allowed males to live longer and to grow longer horns before being harvested. Horn length declined by 6% in sable antelopes, independent of age, suggesting that trophy hunting selected male sable antelopes with smaller horns through time, provided that horn length is heritable. Hunting pressure and trophy value were higher for sable antelopes than for impalas and greater kudus. Accordingly, the decline of horn length in this species was more pronounced. More valuable trophy species, such as sable antelopes, require special attention because they may be exposed to higher hunting pressure, and are therefore more likely to experience a decrease in horn size.